Corporate social responsibility and performance of SMEs in Ho Chi Minh City (Vietnam). (2nd August 2019) - Binh, Tu Van; Tien, Ho Viet
The paper aims to explore the impact of CSR on market-oriented performance and financial performance of SMEs. To do this, the sample selection is 620 SMEs. Results found that there is a significant contribution to the literature review, which the interest of the CSR creates the growth of the market-oriented performance, in which the sales growth, the productivity growth and the labour force growth are enclosed. This study answered the doubts about the impacts of the labour union organisation on SMEs. Although many adjustments on labour union laws, but invisible, this finding does not bring any result for SMEs' performance.